History of Wrestling Sports - Fayzullayev Sherzod Bahodirovich. (Zien Journals, 2022)
The article discusses the history of the Uzbek national sport of wrestling. In the coverage of the text of the article, the research work of scientists was used
Keywords: kurash; history; “gyrrom”; one-on-one